2011
DOI: 10.1149/1.3590748
|View full text |Cite
|
Sign up to set email alerts
|

Performance of Nano Structured Thin Film (NSTF) Electrodes under Partially-Humidified Conditions

Abstract: 3M's Nano Structured Thin Film (NSTF) electrode, being a core-shell catalyst, offers a novel mean to enhance the performance and lower Pt cost in a polymer electrolyte fuel cell (PEFC). In the present work, fuel cell performance of NSTF is reported and the underlying physics dictating NSTF behavior is probed. It was found that NSTF with 0.15 mg Pt /cm 2 Pt loading shows comparable performance to that of a conventional Pt/C electrode with 0.4 mg Pt /cm 2 loading in a highly humidified condition at 80 C. However… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
120
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 79 publications
(122 citation statements)
references
References 25 publications
2
120
0
Order By: Relevance
“…Even so, water management is more challenging on these thin films than on conventional nanoparticulate Pt/C catalysts. 148 …”
mentioning
confidence: 99%
“…Even so, water management is more challenging on these thin films than on conventional nanoparticulate Pt/C catalysts. 148 …”
mentioning
confidence: 99%
“…In addition, it is further postulated that the proton concentration distribution within the water-flooded pores is determined by the electrostatic interactions between the protons and the surface charge of the pore walls [141][142][143]. However, Sinha et al [138] pointed out that, in their study, the NSTF electrode was found to be free of bulk liquid water. They also argued that previous studies using other surfaces such as gold or carbon in liquid water did not show similar proton conduction.…”
Section: Ordered Design Of Catalyst Layermentioning
confidence: 96%
“…In the NSTF, the catalyst support consists of highly-oriented crystalline organic whiskers, onto which the Pt or Pt-alloy catalyst is sputter-coated as a polycrystalline thin film [124,138]. Figure 5 shows cross-sectional SEM images of an NSTF electrode.…”
Section: Ordered Design Of Catalyst Layermentioning
confidence: 99%
See 2 more Smart Citations